Aurophilic interaction-based aggregation of gem-digold(I) aryls towards high spin-orbit coupling and strong phosphorescence - Xiao-Yi Zhai; Liang Zhao (Nature Communications)
Abstract Luminescent gold(I) compounds have attracted intensive attention due to anticipated strong spin-orbit coupling (SOC) resulting from heavy atom effect of gold atoms. However, some mononuclear gold(I) compounds are barely satisfactory. Here, we unveil that low participation of gold in transition-related orbitals, caused by 6s-π symmetry mismatch, is the cause of low SOCs in monogold(I) compounds. To address this issue, we have developed a series of acceptor-donor organogold(I) luminescent compounds by incorporating a gem-digold moiety with various aryl donors. These compounds demonstrate wide-range tunable emission colors and impressive photoluminescence quantum yields of up to 78%, among the highest reported for polynuclear gold(I) compounds. We further reveal that the integration of the gem-digold moiety allows better interaction of gold 6s orbitals with aryl π orbitals, facilitates aryl-to-gold electron transfer, and reduces Pauli repulsion between digold units, finally engendering the formation of aurophilic interaction-based aggregates. Moreover, the strength of such intermolecular aurophilic interaction can be systematically regulated by the electron donor nature of aryl ligands. The formation of those aurophilic aggregates significantly enhances SOC from <10 to 239 cm−1 and mainly accounts for high-efficiency phosphorescent emission in solid state.